PENGARUH MULTIMEDIA BUKU DIGITAL MATERI PEMANASAN GLOBAL TERHADAP HASIL BELAJAR SISWA KELAS VII DI MTs NADHALATUT THALABAH WULUHAN - Mukarromah, Siti Fatimah; Hasbiyati, Haning; Nurjanah, Umi (Universitas Tanjungpura, 2024)
This study investigates the impact of digital multimedia books on students' learning outcomes concerning global warming among seventh-grade students at mts nadhalatut thalabah wuluhan. The research employs a quantitative experimental approach, involving two groups: one utilizing digital books and the other using traditional textbooks for learning. Pre-tests and post-tests were administered to assess students' knowledge before and after the intervention. Results indicate that students who engaged with digital books achieved significantly higher post-test scores (85) compared to those who used conventional textbooks (72). Furthermore, surveys revealed that students found digital books more engaging and motivating, which enhanced their learning experience. Statistical analysis confirmed a significant difference between the two groups (p 0.05). The findings suggest that incorporating digital multimedia resources into education can effectively improve students' understanding of environmental issues, highlighting the need for further integration of technology in teaching practices.